Preliminary Investigations Showing Venous Thromboembolism Recurrence in Patients with Residual Venous Obstruction in Singaporean Population - Sule, Ashish Anil; Er, Chaozer; Chong, Claudia Y.X.; Chin, Han Xin; Chin, Tay Jam (International Journal of Angiology, 2017)
This study aims to determine the association of residual venous obstruction (RVO) with recurrent venous thromboembolism (VTE). A retrospective cohort study was conducted determining if RVO on ultrasonography is associated with recurrent VTE in a Singaporean population. The subjects were identified from the Vascular Diagnostic Laboratory patients' record of Tan Tock Seng Hospital (TTSH), Singapore between 2008 and 2013. All the patients included had RVO after 3 months of anticoagulation. Data such as age, gender, race, thrombus location, etiology, history of malignancy, thrombophilia screen, treatment duration, and follow-up were recorded for analysis. Statistical analysis was performed using Stata/SE 13.1 (StataCorp LLC). The study was approved by the National Healthcare Group Domain Specific Review Board (DSRB), Singapore. Out of the 34 patients who had RVO, 6 (17.6%) developed VTE recurrence. Patients were treated with anticoagulation for a mean time of 24.5 months. The mean follow-up time for VTE recurrence was 25.4 months. Out of the six patients who had VTE recurrence, one had common iliac vein involvement, four had superficial femoral vein and common femoral vein involvement, zero had popliteal vein involvement, and one had calf veins involvement. There was a significant association between thrombophilia (p = 0.0195) and malignancy (p = 0.020) at inclusion with the risk of recurrent VTE. The presence of RVO after 3 months of anticoagulation is likely to increase the risk of VTE recurrence. Larger studies with RVO are needed to evaluate if there is an increased risk of VTE recurrence in the Asian population.
Keywords: DVT; recurrence; residual vein thrombosis; malignancy; venous thromboembolism; thrombophilia; anticoagulation